Effects of six months of combined aerobic and resistance training for elderly patients with a long history of type 2 diabetes - Tan, Sijie; Li, Wei; Wang, Jianxiong (Journal of sports science & medicine, 2012)
This study evaluated the effects of a 6-month combined aerobic and resistance training program on the body composition, glycemic control, lipid profile, and functional capacity of older patients with a long history of type 2 diabetes. 25 subjects (65.9 ± 4. 2 yrs; M/F: 13/12) with a long history of type 2 diabetes (16.7 ± 6.7 yrs) were randomly allocated into either the exercise or control groups. The exercise group trained three sessions a week. Each session consisted of a warm-up period, 30 minutes of moderate aerobic exercise, 10 minutes of resistance training with five leg muscle exercises (two sets of 10-12 repetitions at 50-70% of 1RM for each activity), and a cool-down period. The variables of body composition, glycemic control, lipid profile, and functional capacity were measured before and after the study period. Exercise training decreased waist-hip ratio and body fat of the trained subjects. Concentrations of fasting and 2-hour post-glucose challenge plasma glucose and serum insulin, and glycosylated hemoglobin decreased significantly in the exercise group. Exercise training improved the lipid profile and also increased the leg muscle strength and 6-minute walking distance of the trained subjects. The control group, however, increased their body fat and fasting plasma glucose, while other variables were not changed during the study period. The current results demonstrate that elderly patients with a long history of type 2 diabetes can benefit from the 6-month combined aerobic and resistance training program. Key pointsExercise training is effective for elderly patients with long-term type 2 diabetesExercise prescription for elderly patients with type 2 diabetes should contain both aerobic and resistance activities.